Analisis Bibliometrik Publikasi Manajemen Pendidikan Tinggi - Adiatma, Tini; M, Nursafitra (Jurnal Publisitas, 2023)
This study aims to examine the development of publications related to higher education management. This research aims to discover the development trend of the number of studies and the mapping of research study themes. This study uses bibliometric analysis of data taken with the keyword "management in higher education" with a range of 2012-2023. The results showed that there were 911 scientific articles related to these keywords during 2012-2023. Based on existing publications, there is an increasing trend in the number of publications from year to year. The distribution map of scientific studies related to higher education management based on visualization analysis from VOSViewer shows that the most studied theme in higher education management is related to quality management with a total of 196, followed by the keyword knowledge management with a total of 153 publications, then total quality management with 78 publications. Other topics that are also widely studied in higher education management relate to governance, change management, strategic management. This study provides an overview for researchers and readers in developing relevant research topics in the future.